Factors Affecting Peoples’ Participation on Vulture Conservation from Kaski district of Nepal - KC, Shumsher; Timilsina, YP (Conservation Science, 2013)
Aim This paper explores the social factors affecting local peoples' participation in the vulture conservation. Location Kaski, Nepal. Materials and Methods This study examines attitude of local people towards vulture conservation using a questionnaire survey of 130 households drawn randomly from the two vicinities of the vulture colonies. Key findings The results show that 77.4% of respondents rear an average of 2.97 livestock unit (LSU) per household. More than half of respondents who rear livestock (53.82%) dump livestock carcasses in the open fields. Ethnicity, age, education status, gender, livestock unit and involvement in conservation activities are the most significant predictors for the positive attitudes towards vulture conservation. Those who are young, male, educated, involved in organizations and do not rear livestock are most likely to support vulture conservation. Conservation implications Conservation education is a key for vulture conservation DOI: http://dx.doi.org/10.3126/cs.v1i1.8580 Conservation Science 2013 1(1), 19-26